2003
DOI: 10.1161/01.str.0000098004.26252.eb
|View full text |Cite
|
Sign up to set email alerts
|

4G/4G Genotype of PAI-1 Gene Is Associated With Reduced Risk of Stroke in Elderly

Abstract: Background and Purpose-Plasminogen activator inhibitor type 1 (PAI-1) is the main inhibitor of fibrinolysis, and high levels may increase the risk of cardiovascular disease. The 4G/5G polymorphism affects PAI-1 gene transcription with lower levels of plasma PAI-1 in the presence of the 5G allele. We investigated whether plasma PAI-1 and 4G/5G genotype would predict the occurrence of cardiovascular events at old age. Methods-Relative risks for cardiovascular events and all-cause mortality were obtained in strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 32 publications
5
51
1
2
Order By: Relevance
“…Until recently, PAI-1 was best known for its antifibrinolytic properties. Nevertheless, Hoekstra et al [22] reported that elevated plasma PAI-1 is a strong risk indicator for stroke at old age [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, PAI-1 was best known for its antifibrinolytic properties. Nevertheless, Hoekstra et al [22] reported that elevated plasma PAI-1 is a strong risk indicator for stroke at old age [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that PAI-1 can reduce the diseases risk due to its protective action (5,7).The presence of 4G allele may lead to increased levels of PAI-1 which can cause a reduction in proteolysis and plaque stabilization during the in ammatory process in the brain tissue. Local mechanisms within brain tissue may be involved in the protective effect of PAI-1 and thereby contribute to reduced risk of stroke (5).…”
Section: Discussionmentioning
confidence: 99%
“…Local mechanisms within brain tissue may be involved in the protective effect of PAI-1 and thereby contribute to reduced risk of stroke (5). In the Dutch study, which included people aged 65 to 84 years, it has been shown that the presence of PAI-1 4G/4G genotype reduces the risk of stroke, transient ischemic attack, and death caused by the presence of cardiovascular disease (5). The inhibitory effect of PAI-1 4G/4G genotype on cell migration may lead to a reduced risk of coronary artery disease (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations